Effect of annealing on nanoparticles of hydroxyapatite synthesized via microwave irradiation: Structural and spectroscopic studies - Mishra V.K.; Rai S.B.; Asthana B.P.; Parkash O.; Kumar D. (My University, 2025)
Nanostrips of hydroxyapatite [Ca10 (PO4)6(OH) 2: (HAp)] were synthesized by microwave irradiation using ethylene diamine tetra-acetic acid (EDTA) as a complexing reagent. Precursor of hydroxyapatite obtained by microwave irradiation was subjected to thermogravimetric and differential thermal analysis (TG-DTA). The precursor was calcined at different temperatures viz. 600, 800, 900 and 1000 °C. Crystal structure, microstructures, and nature of bonding of resulting hydroxyapatite were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), FT-IR and Raman spectroscopy techniques. Scanning electron micrographs revealed formation of beautiful nanostrips of HAp in HAp precursor. These nanostrips were stable upto 600 °C as observed in the SEM image of HAp calcined at 600 °C. The width of nanostrips was estimated to be ∼100 nm. As the calcination temperature was increased the surface morphology of the powder changed from strip-like nanostructure to capsule-like nanostructure. Micrographs of the powder samples calcined at 900 and 1000 °C show clearly nanocapsules having diameter around 200 nm. Crystallite size of the precursor and calcined powders estimated by Sherrer's formula agreed with the particle size of corresponding powders determined from SEM micrographs. FT-IR and Raman spectra of HAp powders obtained after calcinations at 600, 800, 900 and 1000 °C further confirmed the formation of pure HAp nanoparticles. © 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.